Maqashid Shariah: Implementation of the Salus Populi Suprema Lex Esto Principle in the Litigation Process During the Covid-19 Pandemic - A. Ummu Fauziyyah; Abd. Qadir Gassing; Marilang Marilang (FITRAH: Jurnal Kajian Ilmu-ilmu Keislaman, 2021)
The Covid-19 pandemic which has been afflicting Indonesians since the beginning of 2020 has a tremendous influence on their lives in variety of ways. The Indonesian government has taken steps to ensure that citizens are protected and that the number of positives is reduced. Keeping the rights of people seeking justice to continue litigating during the Covid-19 pandemic while simultaneously guaranteeing the safety of those infected with the virus is problematic in the field of law enforcement and justice during the Covid-19 epidemic. As a result, the government through the Supreme Court of Indonesia used the Salus Populi Suprema Lex Esto principle which means that people's safety is the highest law by passively using technology in litigation and increasing the supporting facilities for strict health protocols throughout the judiciary, including the Sungguminasa Religious Court. In the context of Maqashid Syariah, the goal of this study was to show and explain the harmony of the use of the Salus Populu Suprema Lex Esto Principle during the Covid-19 Pandemic. This study took a qualitative and empirical approach. The study of primary data source was interviews conducted by judges and court personnel. Collecting, decreasing, presenting, and describing results were all part of the data analysis process. The findings of the investigation revealed that during the Covid-19 epidemic, the government's efforts to uphold justice while preserving the safety of the human soul, such as Maqashid Syariah's of the hifz an-nafs, which is at the primary level was dharuriyyah